Allometric models for the estimation of above- and below-ground biomass of Jatropha curcas L. in semi-arid regions of Southern India. Issue 6 (2nd May 2016) - Rao, G. R.; Prasad, J. V. N. S.; Raju, B. M. K.; Sathi Reddy, P.; Sharath Kumar, P.; Venkateswarlu, B.
ABSTRACT: Jatropha curcas L. (Jatropha) is an important multipurpose tree valued for oil. In India, plans are underway to bring substantial area under this crop for meeting the biofuel requirements of the country. A study was conducted to develop allometric relationships in Jatropha to predict various biomass-related components (above ground and below ground) using easily measurable attributes, viz. collar diameter, tree height, number of branches, crown diameter, and crown depth. Further, it was aimed to establish the reliability of these relationships using an independent dataset obtained from varied management situations. Destructive sampling was carried out during the rainy season of 2011, when Jatropha plants were eight years old. Highly significant allometric relationships (F-values significant at 1% level) were obtained while predicting various biomass components (above, below, and total) using easily measurable attributes with R 2 values ranging from 0.89 to 0.98. Of all the predictors, collar diameter exhibited a highly significant relationship with total dry biomass per plant (R 2 = 0.97). The allometric relationships developed were validated with an independent dataset. The allometric relationships developed would serve as valuable tools for estimating total dry biomass production and carbon sequestration with reasonable accuracy in Jatropha systems, as they are proposed to be taken up in substantial area in the years to come.